PENERAPAN MODEL COOPERATIF SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA PELAJARAN IPA MATERI FUNGSI ALAT INDERA DAN PEMELIHARAANNYA SEMESTER GANJIL DI SDN I TAMAN KECAMATAN SUMBERMALANG KABUPATEN SITUBONDO TAHUN PELAJARAN 2012/2013 - Ruli Darliana; vidya Pratiwi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2013)
The method can be used to improve student learning outcomes is "Cooperative Script is a method of learning in which students work together in pairs and take turns orally summarizing part dipelajari.Jenis part of the material of this study is action research (PTK) .At first cycle , by 60% while the second cycle 90% .Berdasarkan above description of student activity in the classical persiklus continue meningkat.Berdasarkan results of the analysis of student activity. Cooperative learning science with models Script increased in each cycle. In the first cycle as a whole obtained a percentage of student activity () = 68.74%, when adjusted for student activities such as the criteria in Table 3.1, it is classified as a category is quite active. While in the second cycle of learning has increased by 19.79% from 68.74% to 88.75%, in which case the activity of students during the learning Cooperative Script relatively active